Cognitive bio-inspiration - Baharuddin, Nasir (Universiti Putra Malaysia Press, 2013)
The idea of inspiration in specific discovery basically is based from the process of cognitive biological framework and data factual documentation. It tries to justify the notion of thinking and the process of inspiration being developed by certain factual knowledge and thinking systems as a form of an idea. Due to these operations we are able to organize our sensations and conceptions to construct reality.